Eksistensi Asas Praduga Tak Bersalah dalam Penyidikan terhadap Perlindungan Hak Tersangka pada Sistem Peradilan Pidana - Rifdatul Riskiyanti; Syarifuddin Syarifuddin; Moh. Ali Hofi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The principle of the presumption of innocence is a fundamental principle in criminal law that aims to protect the rights of suspects from the beginning of the legal process. This principle is enshrined in the 1945 Constitution and regulated in Article 8 of Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP), which states that a person cannot be considered guilty unless a court decision with permanent legal force declares them guilty. The application of this principle at every stage of examination (investigation, prosecution, and trial) is crucial to ensuring the protection of the rights of perpetrators (suspects or defendants) and preventing the abuse of power that may harm individuals who have not been proven guilty. This research focuses on examining the consequences of violations of this principle in investigations and the protection of suspects’ rights within the criminal justice system, along with efforts to prevent such violations. The method used is a literature review with a juridical-normative approach. The findings indicate frequent neglect of the presumption of innocence, leading to human rights violations. To prevent this, stricter supervision by external monitoring bodies, such as the National Commission on Human Rights, is necessary to safeguard the rights of suspects.